2016
DOI: 10.1016/j.jinorgbio.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Studies on DNA interaction of organotin(IV) complexes of meso-tetra(4-sulfonatophenyl)porphine that show cellular activity

Abstract: The interaction of the diorgano-and triorganotin(IV) derivatives of meso-tetra-(4-sulfonatophenyl)porphine (Me2Sn)2TPPS, (Bu2Sn)2TPPS, (Me3Sn)4TPPS and (Bu3Sn)4TPPS to natural DNA was analysed (together with free meso-tetra-(4-sulfonatophenyl)porphine (H4TPPS) for comparison purposes). Particular attention was paid to (Bu3Sn)4TPPS, a species that shows significant cellular action. Preliminary tests were done on the solution properties of the organotin(IV) compounds (pKA and possible self-aggregation). Spectrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In melanoma cells the treatment with nanomolar concentrations of (Bu 2 Sn) 2 TPPS and (Bu 3 Sn) 4 TPPS is mostly associated, although with different outcomes, to a significant decrease of the expression of integrin and CAM adhesion receptors and especially to the consequent inhibition of the cellular motility. The lipophilicity of the butyl moieties [15] enables (Bu 2 Sn) 2 TPPS and (Bu 3 Sn) 4 TPPS to cross and to intercalate the lipid bilayer of the membrane, to bind phospholipids, glycoproteins and receptors, thus modifying the structure and functionality of the membranes [52], could explain the reported results. Therefore, the decreased expression of integrin and CAM adhesion receptors in treated melanoma cells, could inhibit not only the cellular motility, but also the homologous and heterologous interactions between melanoma and endothelial cells thus preventing the cells from assembling in clumps and the melanoma intravasation, extravasation and metastatic spread.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In melanoma cells the treatment with nanomolar concentrations of (Bu 2 Sn) 2 TPPS and (Bu 3 Sn) 4 TPPS is mostly associated, although with different outcomes, to a significant decrease of the expression of integrin and CAM adhesion receptors and especially to the consequent inhibition of the cellular motility. The lipophilicity of the butyl moieties [15] enables (Bu 2 Sn) 2 TPPS and (Bu 3 Sn) 4 TPPS to cross and to intercalate the lipid bilayer of the membrane, to bind phospholipids, glycoproteins and receptors, thus modifying the structure and functionality of the membranes [52], could explain the reported results. Therefore, the decreased expression of integrin and CAM adhesion receptors in treated melanoma cells, could inhibit not only the cellular motility, but also the homologous and heterologous interactions between melanoma and endothelial cells thus preventing the cells from assembling in clumps and the melanoma intravasation, extravasation and metastatic spread.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, the A375, HT-144 and M74 human melanoma cell lines harbouring the mutation V600E of BRAF, also express the mutated form of several common and different proteins such as ATM in HT-144 cells, instead, in A375 and M74 cells the promoter of TERT is mutated [32][33][34], thus eliciting the reported different sensitivity to the treatment with (Bu 2 Sn) 2 TPPS and (Bu 3 Sn) 4 TPPS. Indeed, the hydrophobic butyl components of the (Bu 2 Sn) 2 TPPS and the (Bu 3 Sn) 4 TPPS, can directly interact with DNA and in particular, the tin of the organotin(IV) compounds can bind not only to the DNA bases but also the functional groups of the DNA grooves and the phosphate of the DNA phosphodiester backbones [11][12][13]15]. Therefore, the high DNA binding affinity of these organotin(IV) compounds and mostly of (Bu 3 Sn) 4 TPPS, elicits the alteration of the DNA conformation [15] and the induction of DNA damage suggested by the increased expression of the full-length PARP-1 as well as by the inhibition of the growth and by the blockage of the cell cycle that we showed in treated melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aydinoglu et al reported that the interaction between DNA and porphyrin‐based tri ‐n‐ butyltin and trimethyltin(IV) derivatives containing meso‐tetra‐(4‐sulfonatophenyl)porphine ( 119 and 120 ) could be due to a synergistic effect resulting from the affinity of tin for phosphates and hydrophobic interactions. [ 143 ] The authors suggested that this interaction could potentially cause DNA conformation changes. A study by Naz et al described the DNA interaction with triorganotin(IV) derivatives of 2,4‐dichlorophenoxyacetic acid ( 121 and 122 ).…”
Section: Mechanism Of Action Of Triorganotin Complexesmentioning
confidence: 99%